Jaminan Kesehatan Dan Keselamatan Kerja Terhadap Sales Promotion Girls (SPG) - Deadora, Gladys (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Abstract There has been a change in the position of women who were originally only in the domestic sector, now turning to the public sector. Conditions in cities that are relatively more heterogeneous open opportunities for women to work in various fields, one of which being Sales Promotion Girls (SPG). In this study, the author explores how the SPG profile and exploitation experienced. This study uses a qualitative approach with observation, interview, and documentation techniques in taking data. Beautiful and attractive appearance is the main capital of this work. SPG in the cigarette industry or drinks are around 21-30 years old with working hours of around 5-7 hours per day. The reason for working in this field is that this field is light work and does not require high education, although on the other hand they only get low wages. Women in this work often experience physical exploitation in the form of sexual harassment and economic exploitation in the form of working hours until evening and the fulfillment of the rights of women workers such as safety factors and the right to leave. With conditions like this, the protection of women working in general and SPG in particular is very important to consider. Occupational Safety and Health (K3) is an effort to prevent accidents and occupational diseases. The goal is to provide occupational safety and health protection to create a safe, healthy workplace so as to minimize the possibility of the risk of accidents and illnesses at work, whether regulated in work agreements or in other regulations in the company. The formulation of the problem is (1) How is the Legal Protection for Occupational Health and Safety Guarantees for Sales Promotions Girls (SPG) reviewed from Law No. 13 of 2003 concerning Labor? The method used in this study is Normative. Keywords: Legal protection, occupational safety and health.